Web and Internet Economics 9th International Conference, WINE 2013, Cambridge, MA, USA, December 11-14, 2013, Proceedings - Chen, Yiling; Immorlica, Nicole (Springer eBooks, 2013)
This book constitutes the thoroughly refereed conference proceedings of the 9th International Conference on Web and Internet Economics, WINE 2013, held in Cambridge, MA, USA, in December 2013. The 36 revised full papers were carefully reviewed and selected from 150 submissions and cover research in theoretical computer science, artificial intelligence, and microeconomics.